Pobreza multidimensional e pobreza monetária no Nordeste: análise comparativa da focalização do Programa Bolsa Família em 2012 - França, Natália Cecília de (2014)
This study compares the targeting of the Bolsa Fam lia Program (BFP) in the Nordeste under the aspects of monetary poverty and multidimensional poverty using the PNAD 2012, and analyzes the headcount ratio of the same. About monetary poverty, households with per capita income below half the minimum wage were classi ed as poor. The multidimensional poor households were identi ed through the methodology proposed by Alkire and Foster (2009), which is based on the Capability Approach. We estimated two logit models to investigate the household socioeconomic characteristics that impact the likelihood of identifying households as poor. The results indicate a high headcount ratio of poverty in the Nordeste under the two approaches used, about 40.